Liquid metal-based elastomer heat conduction enhancement enabled by stretching - Zhang, Rui; Liu, Ming-Yang; Liu, Wei; Li, Zhen-Ming; He, Zhi-Zhu (Case studies in thermal engineering, 2023)
Liquid metal elastomer composite (LMEC) has high thermal conductivity and low mechanical stiffness compared with that filled with rigid microparticles and presents a wide application prospect in wearable electronics and soft robots. This paper develops a coupled thermal-mechanical simulation model to investigate the thermophysical properties of LMECs, demonstrated by the reported experimental and theoretical results. The impacts of filler deformation capacity and geometry sizes on the heat conduction of the elastomer composite are discussed in detail. The simulation results show that a large strain could enhance the effective thermal conductivity of LMECs, When the liquid metal volume ratio is 40%, the effective thermal conductivity of LMEC with 100% strain (1.2W/mK) is twice as high as that without strain (0.6W/mK). The effects of different fillers on the thermal properties of the composites are investigated. When the strain is 100% and the filler volume ratio is 40%, the effective thermal conductivity of LMEC (1.2W/mK) is much higher than that of copper composite (0.25W/mK) since the liquid metal will deform under a large strain. This work provides some simulation support for the application of LMECs in the fields of biomedicine, thermal management and flexible electronics.